2004
DOI: 10.3348/kjr.2004.5.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Acute Necrotizing Encephalopathy in Korean Infants and Children: Imaging Findings and Diverse Clinical Outcome

Abstract: ObjectiveThe purpose of our study was to describe acute necrotizing encephalopathy in Korean infants and children, and we sought to evaluate the prognostic factors.Materials and MethodsAcute necrotizing encephalopathy was diagnosed in 14 Korean infants and children. We retrospectively analyzed the neuroimaging findings including the follow-up changes. The clinical course of the disease was graded, and we evaluated prognostic factors including age, serum level of the aminotransferase, hemorrhage, and localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 26 publications
0
48
0
4
Order By: Relevance
“…8 Sporadic cases have been documented worldwide. 2 To our knowledge, this is the first case of ANE reported in Europe during the 2009 influenza A(H1N1) pandemia and the only one resulting in patient survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Sporadic cases have been documented worldwide. 2 To our knowledge, this is the first case of ANE reported in Europe during the 2009 influenza A(H1N1) pandemia and the only one resulting in patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this imaging technique, eventually associated with DTI, should be advocated as well in the follow-up of these patients to guide the clinical approach and predict the final outcome. 3,8 …”
Section: Discussionmentioning
confidence: 99%
“…1,2 The presence of hemorrhage and localized tissue loss on MRI may suggest a poor prognosis. 9 Reversion of imaging changes to as normal as possible usually suggests a good prognosis. 9 Okumura et al 10 concluded that administration of steroid within 24 hours after the onset was related to better outcome of children with ANEC without brainstem lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Acute viral encephalopathy is often associated with influenza A infection but also has been described in human herpes virus 6 (HHV6), herpes simplex virus (HSV), mycoplasma and measles [2][3][4][5][6][7]. The pathogenesis of viral encephalopathy is not entirely explained but recent studies showed that high levels of cytokines (IL-6, TNF-ɑ), nitrogen oxides (NOx) and histiocytosis in some organs were detected as the cause of inflammation [8,9].…”
Section: Discussionmentioning
confidence: 99%